(untitled) (International Journal of Mathematics and Physics, 2021)
A photovoltaic-thermal (PV-T) hybrid collector evaporator was designed and developed to produce electrical energy and extract thermal energy simultaneously from the panel using the refrigerant circulated the evaporator tubes. The refrigerant absorbs the heat from photovoltaic panels during its phase change from liquid to vapour. The PV-T evaporators deliver both electricity and heat outputs. An R-32 refrigerant-based solar-assisted heat pump water heating system with a rated heat output of 4 kW was developed and tested its performance for producing 150-200 litres of hot water at an average temperature of 60oC. The R-32 refrigerant is selected because it does not have any ozone depletion potential (ODP), and possess very low global warming potential (GWP). The heat pump evaporator was designed to absorb 3.25 kW heat from the panel and maintains the panel below 30oC. The average PV electricity output was 6 kWh, and the requirement was 3.5 kWh. The average excess power of 2.5 kWh has been supplied to the grid, and the average coefficient of performance (COP) of the system was 6.3. For a life span of 25 years, the total equivalent warming impact analysis (TEWI) resulted in a CO2 value of 15,543 kg, which is very much lower than that of conventional systems. The economic analysis performed was reported, and the system is found to be quite suitable for domestic applications and also economically feasible with a payback period of 2.5 years. Keywords: Solar PV-T Collectors, VFD Compressor, Domestic Water Heating.